2004
DOI: 10.1016/j.otohns.2004.06.481
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Patients with Pharyngeal Carcinoma: A Five‐Year Follow‐Up

Abstract: Purpose. The purpose was to evaluate the healthrelated quality of life (HRQL) of patients with pharyngeal carcinoma at diagnosis and after 1 and 5 years in relation to tumor location and treatment modality in a prospective multi-center study.Methods. Eighty-nine patients with pharyngeal carcinoma (mean age, 60.0 years; 76% men) were evaluated using the Eu- Results. Problems with dry mouth and teeth became worse between diagnosis and the 5-year follow-up. Problems with thick secretions and teeth increased betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 0 publications
0
37
1
Order By: Relevance
“…The findings indicate that, although general measures of QOL stabilize after 1 year, little improvement in a number of treatmentrelated symptoms and oropharyngeal function has been demonstrated after 1 year. [17][18][19][20][21][22][23] Persistent symptoms of psychological distress have also been reported. [24][25][26] Although a number of the long-term studies have found stabilization of general measures of QOL at long-term follow-up, a decline in overall QOL 10 years after treatment was found in a small cohort of patients from New Zealand.…”
Section: T He Number Of People In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicate that, although general measures of QOL stabilize after 1 year, little improvement in a number of treatmentrelated symptoms and oropharyngeal function has been demonstrated after 1 year. [17][18][19][20][21][22][23] Persistent symptoms of psychological distress have also been reported. [24][25][26] Although a number of the long-term studies have found stabilization of general measures of QOL at long-term follow-up, a decline in overall QOL 10 years after treatment was found in a small cohort of patients from New Zealand.…”
Section: T He Number Of People In Thementioning
confidence: 99%
“…21 The results from a series of studies that categorized this cohort of 167 patients according to 3 anatomic sites indicated that these oropharyngeal problems tended to be more prevalent, with pharyngeal cancers than with laryngeal or oral cavity cancers. 22,23,54 Oropharyn- geal functional problems were also the most frequent HNCspecific HRQOL deficits 7 to 11 years after treatment for 204 survivors representing 25% of the 821 Norwegian patients who had participated in a trial of conventional and hypofractionated radiation. 24,26 Several long-term studies have indicated that the general health of survivors tends to be worse than that of the general population.…”
Section: Commentmentioning
confidence: 99%
“…Participants who agreed to participate and were eligible signed a consent form which was available in both English and French language [Appendix # 5]. 32 Patients HADS scores were provided to treating physicians so that they could manage the distress symptoms as they thought appropriate.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…This diminution of health-related QOL at 1 year has been reported by others 13,14,17,[33][34][35] and may even have prognostic implications for survival. Fang et al, 22 Nordgren et al, 38 and Mehanna and Morton, 21 for example, showed that patients with head and neck cancer with worse QOL scores had lower survival rates.…”
Section: Commentmentioning
confidence: 99%